2022
DOI: 10.1021/acsphotonics.1c01841
|View full text |Cite
|
Sign up to set email alerts
|

In-Plane Anisotropy in Biaxial ReS2 Crystals Probed by Nano-Optical Imaging of Waveguide Modes

Abstract: Near-field imaging has emerged as a reliable probe of the dielectric function of van der Waals crystals. In principle, analyzing the propagation patterns of subwavelength waveguide modes (WMs) allows for the extraction of the full dielectric tensor. Yet, previous studies have mostly been restricted to high-symmetry materials or narrowband probing. Here, we resolve in-plane anisotropic WMs in thin rhenium disulfide (ReS 2 ) crystals across a wide range of near-infrared frequencies. By tracing the evolution of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
23
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(29 citation statements)
references
References 63 publications
3
23
1
1
Order By: Relevance
“…α-MoO 3 成功演示了天然二维原子晶体中支持双曲声子极化激元,并且双层 转角可以调控极化激元从双曲向椭圆的拓扑转变, 致使研究人员开始寻找更多介 电函数各向异性的天然二维原子晶体 [71,86] 。黑磷具有范德瓦尔斯层状结构,其 二维原子晶体具有很强的面内各向异性 [87][88][89][90][91][92] , 并且被预言有希望支持双曲型等离 激元和激子极化激元 [70,71] 。目前已报导关于黑磷极化激元包括薄层、叠层及转 角的研究大多是基于理论和模拟的结果。 Chunqi Zheng 等人用模拟的方法演示了三层黑磷通过转角来调控其极化激 元双曲线的形态 [93] 。转角双层双曲材料实现从开放(双曲型)到闭合(椭圆型)…”
Section: 转角三层黑磷的双曲极化表面unclassified
“…α-MoO 3 成功演示了天然二维原子晶体中支持双曲声子极化激元,并且双层 转角可以调控极化激元从双曲向椭圆的拓扑转变, 致使研究人员开始寻找更多介 电函数各向异性的天然二维原子晶体 [71,86] 。黑磷具有范德瓦尔斯层状结构,其 二维原子晶体具有很强的面内各向异性 [87][88][89][90][91][92] , 并且被预言有希望支持双曲型等离 激元和激子极化激元 [70,71] 。目前已报导关于黑磷极化激元包括薄层、叠层及转 角的研究大多是基于理论和模拟的结果。 Chunqi Zheng 等人用模拟的方法演示了三层黑磷通过转角来调控其极化激 元双曲线的形态 [93] 。转角双层双曲材料实现从开放(双曲型)到闭合(椭圆型)…”
Section: 转角三层黑磷的双曲极化表面unclassified
“…In terms of nanoimaging and analysis of near-field distribution on plasmonic materials, s-NSOM has been known as a unique and efficient technique to excite polaritons with a sharp metallic tip. Their propagation is detected using a spatial mapping method within a range of infrared–visible wavelengths of light and a spatial resolution of less than 20 nm. , Over the past 10 years, s-NSOM has verified the existence of graphene plasmons, hyperbolic phonon polaritons in van der Waals materials, and topological polaritons in magic-angle twisted two-dimensional nanomaterials. Various transition metal dichalcogenides (TMDs) have been investigated for their excitonic properties, such as anisotropic waveguide modes in ReS 2 , in the mid-infrared and visible to near-infrared (NIR) regions. Furthermore, in the case of the visible range, intensive studies have been conducted that reveal plexciton dynamics combined with nano-optical spectroscopy, which is enhanced due to strong light–matter interaction by coupling of the tip and quantum dots. , Because the sharp metallic tip as an antenna enhances light–matter interaction, additional optical techniques ( e.g. , gratings, patterning, and prisms) are no more necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Meng et al 23 demonstrated the anisotropy of optical nonlinearity in ReS 2 , which exhibited a transition from saturation absorption to anti-saturation absorption by varying the incident light polarization. In addition, there are several reports demonstrating the anisotropy of the out-of-plane optics of ReS 2 and ReSe 2 , 25,26 providing a theoretical basis for the application of all-dielectric nanophotonics. Anton A et al 27 calculated the dielectric constant variation under different polarized light via time-dependent density functional theory and demonstrated the significant biaxial anisotropy attributed to in-plane structures with low symmetry.…”
Section: Introductionmentioning
confidence: 99%
“…demonstrated the anisotropy of optical nonlinearity in ReS2, which exhibited a transition from saturation absorption to anti-saturation absorption by varying the incident light polarization. In addition, there are several reports demonstrating the anisotropy of the out-of-plane optics of ReS2 and ReSe2, 25 , 26 providing a theoretical basis for the application of all-dielectric nanophotonics. Anton A et al 27 .…”
Section: Introductionmentioning
confidence: 99%